A Modern Approach to Minimally Invasive Surgery and Laparoscopic Sterilization in a Chimpanzee - Laura K. Newcomb; Meghan A. Kruse; Larry J. Minter; Craig J. Sobolewski (Case Reports in Veterinary Medicine)
We present the case of Ruby, a 21-year-old hand-reared chimpanzee (Pan troglodytes) who had an obstetric history significant for a premature stillborn infant that was conceived while on oral contraceptive pills, followed by a full term healthy delivery complicated by neonatal demise attributed to inappropriate maternal care. She was recommended for permanent sterilization due to her history of conception while on oral contraceptives. She underwent uncomplicated laparoscopic bilateral tubal ligation. Due to the similar anatomy to humans, human OB/GYN surgical consultants were used. The objective of this case report is to describe a modern technique for approaching and employing laparoscopic surgery in primates. Minimally invasive surgery allows for faster recovery and fewer complications, and has become the preferred approach for surgical intervention in many animals. The information presented in this case report can be expanded to benefit not only Chimpanzees but other large primate species as well. However, subtle anatomical differences among species must be recognized in order to be carried out safely.